Using sediment accumulation rates in floodplain paleochannel lakes to reconstruct climate-flood relationships on the lower Ohio River - Gibson , Derek K.; Bird, Broxton W.; Pollard, Harvie J.; Nealy, Cameron A.; Barr, Robert C.; Escobar, Jaime (Elsevier, 2022)
Late Holocene flood frequencies on the lower Ohio River were investigated using 14C-based sedimentation rates from three floodplain lakes located in Illinois (Avery Lake), Kentucky (Grassy Pond), and Indiana (Goose Pond). Changes in sediment accumulation rates were attributed to variability in the delivery of overbank sediment to each site as controlled by the frequency of Ohio River flooding. Sedimentation rates reached their lowest values in all three lakes between 400 and 1230 CE, indicating a regional reduction in flood frequencies on the lower Ohio River during a period that included the Medieval Climate Anomaly (MCA; ca. 950–1250 CE). Sedimentation rates increased after ca. 1230 CE and remained moderately high through the Little Ice Age (LIA; 1350–1820 CE) until the onset of extensive land clearance during the early 1800s CE. After 1820 CE, sedimentation rates increased further and were higher than any other time during the late Holocene. A comparison of regional paleoclimatic proxies with the above floodplain sedimentation records shows that Ohio River flooding during the late Holocene was responsive to mean-state changes in atmospheric circulation. During the MCA, when clockwise mean-state atmospheric circulation advected southerly moisture from the Gulf of Mexico into the Ohio River Valley primarily in the form of convective rainstorms, flooding on the Ohio River was least frequent. During the LIA, meridional mean-state atmospheric circulation increased the proportion of midcontinental moisture that was sourced from the northern Pacific and Arctic and delivered as snowfall, hence increasing flooding on the Ohio River. We attribute the increase in Ohio River flooding during the LIA to an increase in snowpack volume across the Ohio River Valley and the watershed-scale integration of runoff during spring snowmelt. Following Euro-American land clearance in the early 1800s, flood frequencies decoupled from this relationship and the lower Ohio River became susceptible to frequent flooding, despite a return to ...